Frequência de arraçoamento para alevinos de carpa comum - Bittencourt, Fábio; Neu, Dacley Hertes; Pozzer, Roger [UNESP]; Lui, Tatiane Andressa; Feiden, Aldi; Boscolo, Wilson Rogério (My University, 2013)
The best frequency of feeding for development of common carp fingerlings Cyprinus carpio was determined. Four hundred fish (4.88 ± 1.41 g and 6.72 ± 0.70 cm) were used, distributed in 20 tanks of 250 L each in completely randomized design with four treatments and five replicates. The four feeding strategies adopted were: providing feed once (T1), twice (T2), three (T3) and four times daily (T4) at the same amount being fractionated as described. At the end of 45 days of experiment were carried out measurements of the final weight (FW), final length (FL), weight gain (WG), feed conversion (FC), specific growth rate (SGR) and survivor (SR). It was evaluated the chemical composition of fish carcass: moisture (MT), crude protein (CP), lipids (LP) and ash (AS) and hematological analyzes performed such as erythrocyte (ER), hemoglobin (HG) and hematocrit (HT). There were significant statistical differences (P<0.01) for FW, FL, WG and SGR. For FC and SR there were no statistical differences (P>0.01). For the chemical composition the moisture, lipids and ash showed significant statistical differences (P>0.01), except only for protein (P>0.01) The hematological composition was not influenced by the feed frequency, it was not observed significant statistical difference (P>0.01) of erythrocytes, hemoglobin and hematocrit among dietary treatments. For common carp fingerlings, the provision of ration four times daily provided better final weight, final length, weight gain and specific growth rate without causing changes in the composition and hematological parameters of the fish.
Frequency of feeding for fingerlings of common carp
Keywords: Cyprinus carpio; Feed handling; Fish farm